Effect of lubricant additives on the transition pressure from mild to severe wear for grey cast iron sliding pairs - Kaleli, H; Eyre, T; Ghasripoor, F (ELSEVIER SCIENCE SA LAUSANNE, 1997)
Over the years, a wide variety of chemical compounds have been introduced as additives to improve the performance of oil. The severity of the performance requirement of lubricating oils is rising continuously in terms of extended oil drain intervals, fuel economy, and reduced friction and wear of the components in internal combustion engines. In this work, using a pin-on-disc machine, the effect of various lubricant additives on the friction and wear (transition pressures) of cast iron and laser-cladded sliding partners were studied. Tests were carried out at different velocities and temperatures with different lubricants and the conclusions were demonstrated using different analytical methods such as light microscopy, electron microscopy, surface topography and X-ray fluorescent spectroscopy. Related to the experimental work, the base oil containing ZDDP (zincdialkyldithiophosphate) additive and the fully formulated oil show higher transition pressure than the base oil and base oil + CaSO4 lubricant. At high temperatures and velocities the effectiveness of the additives are less than at low speeds and temperatures. (C) 1997 Elsevier Science S.A.
Keywords: lubricant additives; transition pressure; Engineering; Materials Science